Return dynamics during periods of high speculation in a thinly traded commodity market - Martin T. Bohl; Martin Stefan (Journal of Futures Markets, 2019)
This article studies the effects of speculation in a thinly traded commodity futures market, paying particular attention to periods characterized by high-speculative activity of long–short speculators. Using the speculation ratio as a daily measure for long–short speculation, we employ generalized autoregressive conditional heteroscedasticity regressions to study its impact on return dynamics. Our results for the Chicago Mercantile Exchange feeder cattle futures market suggest that futures returns are predominantly explained by fundamentals, but their volatility is significantly driven by the speculation ratio. This relationship holds for periods of high- and low-speculative activity alike.
Keywords: 330; commodity markets; return dynamics; speculation; thinly traded markets